Come Back Stronger After Suffered for Child Sexual Abuse: A Case Study to Understand the Family Resilience Process - Mochammad Wahyu Ghani; Marya Yenita Sitohang (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2022)
Child sexual abuse (CSA) is quite prevalent in Indonesia, with an increased rate over several years. The negative impacts of CSA have been investigated in several studies and the coping strategies for CSA survivors. However, resilience at the family level is rarely analyzed. This study investigates the resilience process of the CSA survivors' families after they were affected by the incident. Using a qualitative approach, we collected the data by interviewing and observing a family suffering from a CSA incident, the Geulis family (informant pseudonym). Data then were analyzed using thematic analysis with a family resilience model developed by Henry et al. The CSA incident has led to several adverse events in the Geulis (family, including unintended pregnancy, dropping out of school, hesitancy to stay in the hometown, and loss of job and family income. With support from extended family and some organizations, Geulis and her mother were able to find a new place to live and a new job for Geulis’s mother, and Geulis was able to start a new relationship and continue her study for a while. The complex and continuous adaptation process of the Geulis family was also analyzed using the adaptive family systems component. The Geulis family could function normally after experiencing the negative impact of CSA with some adjustment in their life and dynamic process in the family. Environment, including extended family, government, and non-government organizations, supports family resilience.